Sources and levels of rock phosphates on performance of broilers - Bellaver, Claudio; Guidoni, Antônio L.; Albino, Luiz F. T.; Pieniz, Luiz C. (Pesquisa Agropecuaria Brasileira, 2014)
An experiment was carried out with broilers in the initial (7 - 28 days), final (28 - 49 days) and total phase (7 - 49 days), testing three rock phosphate (patos, goiás and tapira), with bicalcium as a standart. In each source the diets were calculated to have 0%; 0.15%; 0.30% and 0.45% of supplemented P, with fixed Ca; P ratio, in isonitrogenous and isoenergetic diets. The pullets were mantained in electric batteries with ten broilers by parcel, in a completely randomized design. The variables were: total weight gain (TWG), feed: gain ratio (FGR), tibial ash (TA), tibial phosphorus (TP) and plasma phosphorus (PP). Goiás phosphate was poorer (P<0.05) than other, and there were no differences (P>0.05) between those phosphates. Goiás phosphate reduced the performance as it was included in the ration. Based on TA the available phosphorus in patos and tapira phosphate range between 54 and 76%. It was concluded that broilers receiving bicalcium, patos and tapira phosphates showed a similar performance, and goiás phosphate reduced the performance as it was included in the ration.